2012
DOI: 10.1007/s11789-012-0048-4
|View full text |Cite
|
Sign up to set email alerts
|

HELP apheresis in hypercholesterolemia and cardiovascular disease: efficacy and adverse events after 8,500 procedures

Abstract: IntroductionLow density lipoprotein (LDL-C) apheresis is a last treatment option for hypercholesterolemic patientsresistant to conservative lipid-lowering therapy. In a retrospective analysis of 8,533 heparin-induced extra-corporeal LDL precipitation apheresis treatments (HELP), we evaluated the efficacy of LDL reduction, the rate of adverse events, and the progression of atherosclerosis.MethodsBetween July 1992 and April 2009, we performed 8,533 HELP apheresis therapies in patients with familial hypercholeste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 29 publications
1
12
0
1
Order By: Relevance
“…n Side effects Side effects from all lipoprotein apheresis meth ods are observed in approximately 5% of the sessions [33,[53][54][55]. This is in agreement with our own practice.…”
Section: Experience With Lipoprotein Apheresis N Effects On Lipid Consupporting
confidence: 87%
See 1 more Smart Citation
“…n Side effects Side effects from all lipoprotein apheresis meth ods are observed in approximately 5% of the sessions [33,[53][54][55]. This is in agreement with our own practice.…”
Section: Experience With Lipoprotein Apheresis N Effects On Lipid Consupporting
confidence: 87%
“…n Effect on cardiovascular events Several papers describe an effective reduction in the incidence of new cardiovascular events and/or nonprogression or even regression (documented by angiography) when comparing prior years with those under apheresis treatment [10,53,54,[58][59][60][61][62]. It must be admitted that the apheresis treatment does not completely prevent new events.…”
Section: Experience With Lipoprotein Apheresis N Effects On Lipid Conmentioning
confidence: 99%
“…64 Clinical evidence has suggested that long-term lipoprotein apheresis can contribute to atherosclerotic plaque regression and stabilization. 65,66 Although apheresis might increase longevity in patients with HoFH and decrease CVD morbidity in patients with HeFH who are refractory or intolerant to statins, 67 no hard efficacy data from double-blind, randomized trials exists and, owing to several reasons (primarily ethical), such studies will probably not be performed. 68 In very young patients with HoFH, venous access can be difficult to find, which can lead to treatment postponement for 1-2 years: the youngest patient with HoFH treated with statin therapy only underwent apheresis at the age of 3 years; 69 as of 2015, 12 years later, the patient remains alive and with no cardiovascular events.…”
Section: Apheresismentioning
confidence: 99%
“…Thompson et al [129], published the FH Regression Study, in which they assessed 20 patients with FH undergoing dextran sulfate LA, compared to 19 FH patients who were relying on medication. Although the apheresis group showed marked reduction in both LDL and Lp(a) levels, the progression of atherosclerosis (followed angio- apheresis treatments, with an average follow-up period of 7.0 ± 5.2 years, indicated that LA was successful in reducing LDL levels (average reduction of 63.49 ± 7.1%) and produced low levels of coronary intervention [131].…”
Section: Effect Of Ldl Apheresis On Cvd Outcomesmentioning
confidence: 95%